Authentic Leadership and School Effectiveness: The Mediating Role of Affective Commitment - Kamizhi Mulambwa Ephraim; Clement Mwaanga (Yayasan Lembaga Studi Makwa, 2026)
This study examined the mediating role of affective commitment in the relationship between authentic leadership and organisational effectiveness in public secondary schools in Western Province, Zambia. Despite growing interest in authentic leadership, no prior study has tested affective commitment as a simultaneous mediator linking it to both organisational effectiveness and job satisfaction in a Zambian school-level model, a gap this study addresses. Grounded in Authentic Leadership Theory and Social Exchange Theory, a sequential explanatory mixed-methods design was employed. Quantitative data were collected from 402 teachers across five districts using the Authentic Leadership Questionnaire, the Minnesota Satisfaction Questionnaire (MSQ), and the Survey of Organisational Effectiveness. Structural Equation Modelling with bootstrapped mediation analysis was supplemented by thematic analysis of semi-structured interviews with 20 Headteachers. The SEM demonstrated excellent model fit and found that authentic leadership exerted a strong direct effect on organisational effectiveness (β = 0.433, p < 0.001) and an exceptionally strong effect on affective commitment (β = 0.963, p < 0.001). Affective commitment partially mediated the leadership effectiveness relationship, accounting for 46% of the total effect (indirect β = 0.364). Contrary to expectations, job satisfaction had no significant direct effect on organisational effectiveness (β = 0.009, p = 0.825). The study proposes what may be termed a ‘heart-first’ pattern of school effectiveness, in which affective commitment, rather than job satisfaction, appears to be the primary psychological mechanism through which authentic leadership is associated with school performance and advances culturally contextualized implications for principal leadership development, suggesting that leadership preparation, teacher retention, and school improvement policy in comparable Sub-Saharan African educational contexts should prioritise the cultivation of affective commitment rather than job satisfaction alone.